The Insertion Domain of Mti2 Facilitates the Association of Mitochondrial Initiation Factors with Mitoribosomes in Schizosaccharomyces pombe - Ying Luo; Jürg Bähler; Ying Huang (Biomolecules)
Translation initiation in mitochondria involves unique mechanisms distinct from those in the cytosol or in bacteria. The Schizosaccharomyces pombe mitochondrial translation initiation factor 2 (Mti2) is the ortholog of human MTIF2, which plays a vital role in synthesizing proteins in mitochondria. Here, we investigate the insertion domain of Mti2, which stabilizes its interaction with the ribosome and is crucial for efficient translation initiation. Our results show that the insertion domain is critical for the proper folding and function of Mti2. The absence of the insertion domain disrupts cell growth and affects the expression of genes encoded by mitochondrial DNA. Additionally, we show that Mti2 physically interacts with the small subunits of mitoribosomes (mtSSU), and deletion of the insertion domain dissociates mitochondrial initiation factors from the mitoribosome, reducing the efficiency of mitochondrial translation. Altogether, these findings highlight the conserved role of the insertion domain in facilitating translation initiation in fission yeast and thus reveal shared principles of mitochondrial translation initiation in both fission yeast and humans.